The Correction of Quantum Tunneling Rate and Entropy of Non-Stationary Spherically Symmetric Black Hole by Lorentz Breaking - Yu-Zhen Liu; Xia Tan; Jie Zhang; Ran Li; Shu-Zheng Yang (Universe, 2023)
With the introduction of CFJ correction term, Chiral correction term, and aether-like correction term, based on Lorentz breaking, WKB approximate, and quantum tunneling radiation theory of black holes, the modified fermion dynamics equation is studied in the general non-stationary spherically symmetric black hole space-time, and the new modified expressions of the fermion tunneling rate, the Hawking temperature, and the Bekenstein–Hawking entropy of the black hole are obtained. This black hole has both thermal and non-thermal radiation. In this article, the influence of Lorentz breaking on the energy levels of Dirac particles was also studied, and the distribution characteristics of Dirac energy levels in the space-time and the maximum value of the crossing of positive and negative energy levels were obtained. The necessary discussion and the explanation of the corresponding results are made.